2021
DOI: 10.1038/s41598-021-92388-5
|View full text |Cite|
|
Sign up to set email alerts
|

In silico comparison of SARS-CoV-2 spike protein-ACE2 binding affinities across species and implications for virus origin

Abstract: The devastating impact of the COVID-19 pandemic caused by SARS–coronavirus 2 (SARS-CoV-2) has raised important questions about its origins and the mechanism of its transfer to humans. A further question was whether companion or commercial animals could act as SARS-CoV-2 vectors, with early data suggesting susceptibility is species specific. To better understand SARS-CoV-2 species susceptibility, we undertook an in silico structural homology modelling, protein–protein docking, and molecular dynamics simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 81 publications
(94 reference statements)
3
75
0
1
Order By: Relevance
“…Animal models have been used to explore various disease aspects of SARS-CoV-2 as well as for establishing the safety and efficacy of many interventional measures [13]. Studies have shown the high binding affinity of SARS-CoV-2 spike protein to hamster ACE2 receptor [14]. The virus replicates to high titre in the respiratory tract of Syrian hamsters and causes pneumonia [15].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been used to explore various disease aspects of SARS-CoV-2 as well as for establishing the safety and efficacy of many interventional measures [13]. Studies have shown the high binding affinity of SARS-CoV-2 spike protein to hamster ACE2 receptor [14]. The virus replicates to high titre in the respiratory tract of Syrian hamsters and causes pneumonia [15].…”
Section: Introductionmentioning
confidence: 99%
“…What digital twin technology can particularly bring to the desired picture is replacing (at least partially) the generally expensive and resource-intensive laboratory experiments with in silico simulations ( Figure 3 ); cf. [ 15 ], which used computer models of the SARS–coronavirus 2 or SARS-CoV-2 spike protein and the angiotensin converting enzyme 2–ACE2 receptors of different human and animal species to conduct an in silico comparison of protein receptor binding affinities across species. Given the intricacy and complex interconnections of the diverse types of systems within the human body, establishing an adequate, complete human digital twin may be far from reality.…”
Section: Digital Twins In Personalised Medicinementioning
confidence: 99%
“…Mutations in the spike (S) protein are responsible for these phenotypes by modifying neutralising epitopes and/or increasing the affinity for the human angiotensin converting enzyme 2 (hACE2) receptor (Gan et al, 2021). In addition to enhance the transmissibility between humans, these mutations can also alter the susceptibility of other host species of the virus, therefore broadening the animal reservoir (Conceicao et al, 2020;Liu et al, 2021;Piplani et al, 2021). Also, animals are well-known coronavirus reservoirs (Menachery et al, 2017).…”
Section: Introductionmentioning
confidence: 99%